Secondary metabolite credentials of Evolvulus alsinoides by high performance thin layer chromatography (HPTLC) - Gomathi, Duraisamy (Editorial Department of Journal of Biomedical Research, 2012)
Plants and plant-based products are the bases of many modern pharmaceuticals that are current in use today for various diseases. The aim of the study was to investigate the biochemical constituents and high performance thin layer chromatography (HPTLC) finger printing of the ethanolic extract of Evolvulus alsinoides. Phytochemical screening was done by standard procedures and HPTLC method was also established to analyze alkaloids, flavonoids and phenolic compounds from the ethanolic extract of Evolvulus alsinoides. Preliminary phytochemical screening showed that ethanol extracted more secondary metabolites than other solvents. HPTLC fingerprinting analysis showed the presence of various alkaloids, flavonoids and phenols (quercetin) in the ethanolic extract. It can be concluded that Evolvulus alsinoides may serve as a source of potent antioxidants that may be used in the prevention of various diseases such as cancer, diabetes and cardiovascular diseases due to the presence of phenolic compounds. HPTLC finger print of Evolvulus alsinoides may be useful in the differentiation of the species from adulterants and act as a biochemical marker for this medicinally important plant in the pharmaceutical industry and plant systematic studies.